Effects of environment lighting on the growth, photosynthesis, and quality of hydroponic lettuce in a plant factory - Zhang, Xin; He, Dongxian; Niu, Genhua; Yan, Zhengnan; Song, Jinxiu (International Journal of Agricultural and Biological Engineering, 2018)
Leafy vegetable production under controlled environment using artificial lighting has many advantages over conventional greenhouses and open-field production. However, high initial investment and operation costs are restricting the wide application of this technology. In order to design an optimal artificial lighting environment for lettuce production, effects of different combinations of light intensity, photoperiod, and light quality on growth, quality, photosynthesis, and energy use efficiency of lettuce (Lactuca sativa L. cv Ziwei) were investigated under a closed plant factory. Lettuce transplants were grown under photosynthetic photon flux density (PPFD) at 150 µmol/m2·s, 200 µmol/m2·s, 250 µmol/m2·s, and 300 µmol/m2·s provided by fluorescent lamps (FL) with a red to blue ratio (R:B ratio) of 1.8 and light-emitting diode (LED) lamps with R:B ratio of 1.2 and 2.2, in combination with photoperiod of 12 and 16 h/d. In order to examine the “long term” photosynthetic characteristics, net photosynthetic rates of hydroponic lettuce leaves were continuously measured for 2 days (15th and 16th day after transplanting) before harvest. There was no difference in leaf fresh weight (FW) between PPFD of 250 µmol/m2·s and 300 µmol/m2·s with photoperiod of 16 h/d, regardless of light quality, and same results showed in contents of nitrate, soluble sugar, and vitamin C, respectively. The results of continuous measurements of net photosynthetic rate of lettuce leaves before harvest indicated that plants grown at PPFD of 250 µmol/m2·s had consistently higher compared to those grown at PPFD of 300 µmol/m2·s. Combining the results from growth, photosynthesis, quality, and energy consumption, it can be concluded that PPFD at 250 µmol/m2·s with photoperiod of 16 h/d under LED with R:B ratio of 2.2 is a suitable light environment for maximum growth and high quality of commercial lettuce (cv. Ziwei) production under indoor controlled environment.Keywords: plant factory, daily light integral, artificial light, photosynthetic photon flux density, net photosynthetic rate, energy use efficiencyDOI: 10.25165/j.ijabe.20181102.3420Citation: Zhang X, He D X, Niu G H, Yan Z N, Song J X. Effects of environment lighting on the growth, photosynthesis, and quality of hydroponic lettuce in a plant factory. Int J Agric & Biol Eng, 2018; 11(2): 33–40.